ROLE OF PICCHA BASTI IN THE MANAGEMENT OF RAKTARSHA - Mohammad Rashid; Anil Bhardwaj; Kulwant Singh Himaliyan; Sanjeev Sharma; Ramesh Arya (International Journal of Applied Ayurved Research, 2015)
Raktarsha is one of the commonest troublesome diseases of modern era. Main etiological factors are faulty food habits and sedentary life style. Patients want quick relief but at the same time not interested for surgery due to severe post operative pain. In such conditions best alternative is Piccha Basti , which is a painless simple procedure and relieves the symptoms.Keeping this fact in mind the present study was planned. This clinical study was prospective and unicentral work designed to assess the efficacy of Piccha Basti in the management of Raktarsha. It was carried out in single group with a sample size of 10 patients. Ethical clearance from IEC was obtained. In this randomized clinical trial, patients with age ranged -from 20-70 years of either sex were selected strictly following the inclusion and exclusion criteria. Piccha Basti was prepared and administrated as per the textual guidelines. Standard criteria was set for evaluation. Analysis revealed statistically highly significant results on all the variables of assessment criteria. 90% patients were markedly improved. Percentage relief in Proctorrhagia was 100%.It reveales that Piccha Basti has a tremendous role in the management of Raktarsha.However, trials on larger sample size are required.